2019
DOI: 10.2196/11188
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Web-Based Ratings on Patient Choice of a Primary Care Physician Versus a Specialist: Randomized Controlled Experiment

Abstract: Background Physician review websites have empowered prospective patients to acquire information about physicians. However, little is known about how Web-based ratings on different aspects of a physician may affect patients’ selection of physicians differently. Objective The objectives of this study were to examine (1) how patients weigh ratings on a physician’s technical skills and interpersonal skills in their selection of physicians and (2) whether and how people’s ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Besides acquiring information through active search, people are also incidentally exposed to health information online [ 15 ]. Health information received online not only fills an information gap but also influences people’s health decision making [ 16 , 17 ]. Besides the internet, personal experiences serve as a prominent means to acquire information.…”
Section: Introductionmentioning
confidence: 99%
“…Besides acquiring information through active search, people are also incidentally exposed to health information online [ 15 ]. Health information received online not only fills an information gap but also influences people’s health decision making [ 16 , 17 ]. Besides the internet, personal experiences serve as a prominent means to acquire information.…”
Section: Introductionmentioning
confidence: 99%
“…The present results are the first to indicate that written pre-consultation information about physicians' skills, which is increasingly available and consulted online, does not only affect patients' selection of a physician [1,4], but also patients' pre-consultation trust and treatment outcome expectancies. Trust and outcome expectancies in turn are known to impact the patient-physician relationship [5,6] and treatment adherence and outcomes [10,11,[13][14][15][16] and are considered core mechanisms of placebo effects [24].…”
Section: Discussionmentioning
confidence: 57%
“…This information may contain objective information (e.g., about physicians' competencies), provided by, for example, a hospital website [2], or it may consist of patients experiences (e.g., of empathic skills) placed on social media or public physician rating websites [3]. While previous research found that such online information may influence patients' choice of physician [1,4], it is largely unknown how such information may affect patients' trust in physicians and treatment outcome expectancies, which are important predictors of treatment outcomes. Particularly the communication of physicians' competence and empathic skills may impact whether patients experience their physician as trustworthy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have explored the factors that patients pay attention to in the process of consultation through behavioral experiments (Li and Hubner, 2019), qualitative analysis (Asanad et al, 2018;Detz et al, 2013;Lagu et al, 2019;Menon, 2017;Orhurhu et al, 2019;Ryskina et al, 2020), quantitative analysis (Li et al, 2019a) or text mining methods (Hao and Zhang, 2016;Liu et al, 2019), the topics analyzed in these studies are not sufficiently Physician review analysis comprehensive. We list some of the factors that have already been discovered or studied in Table 1.…”
Section: Literature Review 21 Physician Reviewsmentioning
confidence: 99%